A survey of students' motivation for learning English - Vijchulata, Boosakorn; Lee, Gan Siowck (SAGE Publications, 1985)
A survey to study the students' motivation for learning English in Universiti Pertanian Malaysia (UPM) was carried out in the second semester of the 1982/83 academic year. The subjects of this study consisted of approximately a thousand students from all the different faculties in UPM who were taking the five English proficiency courses (BB 051, BB 151, BB 251, BB 253, BB 254) and one special English course BB 252. The students' responses were analyzed in terms of frequency distributions; and where appropriate, cross-tabulation, Pearson's product-moment correlation, t-test and multiple range test were also used to establish relationships among some of the factors under study. It is found that UPM students are both integratively and in strumentally oriented in the English language-learning task. In terms of motivational intensity, students from the more advanced English courses seem to be more motivated than those from the lower level or more basic courses. In general, UPM students expressed a strong desire to learn English. Overall, the majority of the students perceived their lecturers as encouraging towards their English language- learning task, as compared to their perception of their parents in the same respect.